EpCAM Is a Surface Marker for Enriching Anterior Pituitary Cells From Human Hypothalamic-Pituitary Organoids - Kodani, Yu; Kawata, Miho; Suga, Hidetaka; Kasai, Takatoshi; Ozone, Chikafumi; Sakakibara, Mayu; Kuwahara, Atsushi; Taga, Shiori; Arima, Hiroshi; Kameyama, Toshiki; Saito, Kanako; Nakashima, Akira; et al. (Frontiers in Endocrinology, 2022)
Human stem cell-derived organoid culture enables the in vitro analysis of the cellular function in three-dimensional aggregates mimicking native organs, and also provides a valuable source of specific cell types in the human body. We previously established organoid models of the hypothalamic-pituitary (HP) complex using human pluripotent stem cells. Although the models are suitable for investigating developmental and functional HP interactions, we consider that isolated pituitary cells are also useful for basic and translational research on the pituitary gland, such as stem cell biology and regenerative medicine. To develop a method for the purification of pituitary cells in HP organoids, we performed surface marker profiling of organoid cells derived from human induced pluripotent stem cells (iPSCs). Screening of 332 human cell surface markers and a subsequent immunohistochemical analysis identified epithelial cell adhesion molecule (EpCAM) as a surface marker of anterior pituitary cells, as well as their ectodermal precursors. EpCAM was not expressed on hypothalamic lineages; thus, anterior pituitary cells were successfully enriched by magnetic separation of EpCAM+ cells from iPSC-derived HP organoids. The enriched pituitary population contained functional corticotrophs and their progenitors; the former responded normally to a corticotropin-releasing hormone stimulus. Our findings would extend the applicability of organoid culture as a novel source of human anterior pituitary cells, including stem/progenitor cells and their endocrine descendants.